2020
DOI: 10.2337/db200057
|View full text |Cite
|
Sign up to set email alerts
|

Translational Factor eIF4G1 Regulates Glucose Homeostasis and Pancreatic β-Cell Function

Abstract: Rotarod test was performed to assess locomotive coordination of C57/Bl6 WT and βeIF4G1KO mice, over the course of 4 days (n=7, 5) (A). Body weight of 2-months-old male (B) and female (C) Rip-Cre WT, eIF4G1f/+, βeIF4G1HET, eIF4G1f/f and βeIF4G1KO (n=7, 8, 11, 7, 11 males; n=5, 5, 6, 5, 7 females). In vivo glucose tolerance (2 g/kg glucose, i.p.) was performed on 5months-old Male C57/Bl6 WT, eIF4G1f/f and βeIF4G1KO (n=7, 5, 5). Area under curve (AUC) of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…18 Last but not least, it was recently shown that eIF4G1, the scaffolding protein that binds eIF4E and eIF4A to form the cap-binding complex, eIF4F, is critical for beta cell function and glucose homeostasis. 78 Beta-cell specific eIF4G1-KO mice displayed glucose intolerance and deficits in insulin secretion. 78 Altogether these data demonstrate an essential role for the translational control as well as specific initiation factors in glucose homeostasis, beta cell function and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Last but not least, it was recently shown that eIF4G1, the scaffolding protein that binds eIF4E and eIF4A to form the cap-binding complex, eIF4F, is critical for beta cell function and glucose homeostasis. 78 Beta-cell specific eIF4G1-KO mice displayed glucose intolerance and deficits in insulin secretion. 78 Altogether these data demonstrate an essential role for the translational control as well as specific initiation factors in glucose homeostasis, beta cell function and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…78 Beta-cell specific eIF4G1-KO mice displayed glucose intolerance and deficits in insulin secretion. 78 Altogether these data demonstrate an essential role for the translational control as well as specific initiation factors in glucose homeostasis, beta cell function and lipid metabolism. We thus believe that the identification of specific eIF2A function in the development of obesity and metabolic syndrome adds to our understanding of these processes and bears promise for further identification of specific and direct eIF2A targets, responsible for these changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For specific subsets of experiments (quantitative PCR in Supplementary Fig. S7G-O [ 20 ] and electrophysiology in Supplementary Fig. S6A and B [ 20 ]), islets were maintained overnight in 10 mM glucose instead of our routine 5 mM glucose.…”
Section: Methodsmentioning
confidence: 99%
“…S7G-O [ 20 ] and electrophysiology in Supplementary Fig. S6A and B [ 20 ]), islets were maintained overnight in 10 mM glucose instead of our routine 5 mM glucose. Naïve untested insulin content was measured from 10 islets from each mouse, using Ultrasensitive Mouse Insulin ELISA kits (ALPCO, AB_2792981) and normalized by DNA content with PicoGreen dsDNA assay kit.…”
Section: Methodsmentioning
confidence: 99%